Students' Physical Activity Profiles According to Children's Age and Parental Educational Level - Inés M. Muñoz-Galiano; Jonathan D. Connor; Miguel A. Gómez-Ruano; Gema Torres-Luque (MDPI AG, 2021)
The aim of this study was to identify different profiles of physical activity (PA) behaviors according to the school student's age stage and their parents' or guardians education level. Seven hundred twenty-seven students and parents of different educational stages were invited to take part in this study. The participants included, Preschool (1 to 5 years old), Primary School (6 to 11 years old), Secondary School (12 to 15 years old), and High School (16 to 18 years old). A questionnaire to assess the educational level of parents (low, intermediate, and high) and their child's PA level and sedentary behaviors across various age stages was administered. The results showed a number of different physical activity profiles for preschool (4), primary (6), secondary (7) and high school (2) students. Primary and secondary school children's behavioral profiles were reported to differ significantly between both physical activity levels and sedentary behaviors, while preschool students' behavioral profiles only differed between sedentary behaviors. Higher parental education was most prevalent in clusters with significantly higher levels of PA in primary and secondary students, while there were equivocal trends for parental education level influencing behavioral profiles of high school students. These findings suggest there is some association between the behavioral profiles of student's physical activity and sedentary behavior, and parental education level, most noticeably during the early to middle age stages.